Adult education and livelihood : woman as agents of change - Pant, Mandakini (2004)
Suggests ways in which savings, enterprise and basic literacy are used as tools for building the capacity of grassroots women's collectives to enhance their livelihood and improve their quality of life; and, the impact of these on women's collectives.